BambuFlex – a Digital Form-Finding Tool for Curved Bamboo Structure based on Indonesian Bamboo - Hardiansyah, Wisnu Agung; Kusumawanto, Arif; Irawati, Inggar Septhia (Departement of Architecture, Universitas Islam Indonesia, 2024)
Contemporary bamboo buildings with curved structures have recently gained popularity despite their challenging nature to design and construct. The inherent material characteristic must be incorporated into the design process, often called form-finding. The typical form-finding approach in Indonesia incorporates physical mediums known to be complex and laborious. On the contrary, the digital medium is rarely used due to the lack of tools capable of performing quick and accurate form-finding while incorporating local bamboo and bending methods. This paper showcases BambuFlex, a digital tool that performs quick and accurate form-finding based on local bamboo and bending approaches in Indonesia. The algorithm’s capability was validated by comparing its accuracy and real-time material feedback with the conventional physical method. The result shows that BambuFlex is able to provide accurate and materially informed form-finding, but it has some limitations. To conclude, BambuFlex can complement the conventional physical form finding, allowing architects to explore more design alternatives rapidly. Keywords: bending-active bamboo structure, digital form-finding, local bending method